The effect of electric fields on hyaline cartilage: an in vitroand in silicostudy (2019)
Abstract: Hyaline cartilage is a dense connective tissue with low self-healing capacity when is affected by degenerative pathologies. Therefore, electrical stimulation has been proposed as a possible non-invasive alternative therapy to enhance the restoration of the cartilaginous tissue. Accordingly, this work presents a combined computational and experimental approach to understand better the hyaline cartilage biology and its response to electrical stimulation using different in vitro models. On the one hand, a mechanobiological model was developed to simulate the endochondral ossification process. On the other hand, the electrical stimulation on hyaline cartilage was evaluated in three different scenarios. Initially, cell proliferation and glycosaminoglycans synthesis of chondrocytes, cultured in monolayer and stimulated with electric fields, was analyzed. Then, a histomorphometric analysis was performed to chondroepiphysis explants that were electrically stimulated. Finally, the effects of the electric fields on chondrogenic differentiation of mesenchymal stem cells cultured in hydrogels was assessed. The results indicated that electrical stimulation is a promising biophysical stimulus, due to the fact that this type of stimulation enhances the viability and the proliferation of cells, induces morphological changes in the chondrocytes, and stimulates the synthesis of the main molecules that compose the hyaline cartilage, such as SOX-9, glycosaminoglycans and aggrecan. Moreover, this project is the first step towards the implementation of an alternative biophysical stimulus that modifies the cellular dynamics of growth plate chondrocytes in ex vivo conditions. Additionally, this study highlights the potential effect of electric fields to induce the chondrogenesis process of mesenchymal stem cells cultured in basal conditions. Overall, the assessment of electrical stimulation on chondrocytes, tissues and scaffolds is a useful tool that may contribute to the current knowledge of regenerative therapies focused on hyaline cartilage healing.